3D N-doped hybrid architectures assembled from 0D T-Nb2O5 embedded in carbon microtubes toward high-rate Li-ion capacitors. (February 2019) - Hemmati, Sahar; Li, Ge; Wang, Xiaolei; Ding, Yuanli; Pei, Yu; Yu, Aiping; Chen, Zhongwei
Abstract: Herein, a unique nitrogen-doped T- Nb2 O5 /tubular carbon hybrid structure in which T -Nb2 O5 nanoparticles are homogeneously embedded in an in-situ formed nitrogen-doped microtubular carbon is synthesized, utilizing a facile and innovative synthesis strategy. This structure addresses the poor electron conductivity and rate capability that hinder T -Nb2 O5 's promise as an anode for Li-ion devices. Such a distinctive structure possesses a robust framework that has ultrasmall active nanocomponents encapsulated in highly conductive carbon scaffold with hollow interior and abundant voids, enabling fast electron/ion transport and electrolyte penetration. Moreover, nitrogen-doping not only ameliorates the electronic conductivity of the heterostructure, but also induces pseudocapacitance mechanism. When evaluated in a half-cell, the as-prepared material delivers a specific capacitance of 370 F g −1 at 0.1 A g −1 within 1–3 V vs. Li/Li + and excellent cyclability over 1100 cycles. A high energy density of 86.6 W h kg −1 and high power density of 6.09 kW kg −1 are realized. Additionally, a capacitance retention as high as 81% after 3500 cycles is achieved in an Li-ion Capacitor (LIC) with activated carbon as the cathode and nitrogen-doped T- Nb2 O5 /tubular carbon as the anode. Graphical abstract: A high-rate Li+ intercalation pseudocapacitance material is synthesized by a facile approach. The unique morphological features of N-doped T-Nb2 O5 @C results in a remarkably high capacitance of 370 F g −1 at 0.1 A g −1 and 81% capacitance retention after 1100 cycles in a half-cell. Furthermore, the hybrid LIC device exhibits maximum energy density of 86.6 W h kg −1 and energy density of 58.7 W h kg −1, when discharged in 48 s Highlights: The orthorhombic crystalline phase of Nb2 O5 nanoparticles embedded in a tubular carbon structure is successfully synthesized. A notable synergistic effect is achieved emerging from ingrained metal oxide nanoparticles in a conductive scaffold doped with nitrogen. The nanocomposite exhibits a reversible capacitance of 370 F g −1 within 1–3 V vs. Li/Li +. An LIC device based on the synthesized nanocomposite and activated carbon delivers 58.7 W h kg −1 at 3.84 kW kg −1 .